The sound sense of poetry - Robinson, Peter 1953- (Cambridge University Press, 2018)
What real role can poetry have in the world? How are its truths created by the words and sounds chosen by the poet and by the way readers respond to them? Acclaimed poet Peter Robinson brings his knowledge of poetic art to the understanding of the reader's contribution in enabling poetry to play its part in life. Emphasising the value of individual writers' and readers' interactions, together with such key matters as meter and rhythm, voicing and form, rhyme and syntax, Robinson shows how poems engage in speech performances such as promising, justifying, excusing, and explaining - including the telling of truths. Illustrated with detailed readings of poems by, among others, Jonson, Marvell, Blake, Wordsworth, Coleridge, Tennyson, Christina Rossetti, Dickinson, Kipling, Basil Bunting, Frank O'Hara, Tony Harrison, and Denise Riley, this book shows how important poetry is as a means to do things with words and make things happen
Title from publisher's bibliographic system (viewed on 14 Sep 2018)
Keywords: Poetics; Poetry / Social aspects; Englisch; Poetik; Lyrik; Literaturtheorie